Telemonitoring Padatan Terlarut pada Filtrasi Air Limbah Laundry Menggunakan Sensor TDS dan Sensor pH untuk Media Budidaya Tanaman Hidroponik Berbasis Mikrokontroler - Nadhea Lulu Luqyana; Farida Arinie; Azam Muzzakhim (Politeknik Negeri Malang, 2021)
In this study, a tool for telemonitoring dissolved solids was designed in the filtration of laundry wastewater which is used as a hydroponic planting medium, pH sensor, and TDS sensor to measure and obtain dissolved solids data that affect the plant growth process, then these data will be processed by the Arduino microcontroller. Nano so that the final result will be stored in the database and sent wirelessly via Wemos D1 so that it can be displayed in the android application. The research that has been done, obtained the results of the measurement value of dissolved solids of laundry wastewater before filtering for a Ph value of 6.63 and a solution concentration of 250 ppm. After twice filtration, the dissolved solids for Ph were 6.32 and TDS was 1276 ppm. Based on this study, the results of telemonitoring the average dissolved solids of laundry waste filtration water after being used as a hydroponic planting medium with a PH value of 6.86 and a TDS of 681 ppm. Because the dissolved solids value of the planting medium is not in accordance with the minimum standard of use in hydroponic agriculture (PH = 6.5; solution concentration = 850 ppm), it can be concluded that the use of laundry wastewater filtration causes plants to grow slowly and abnormally (stunted).